INFLUENCE OF THE COMBINATION OF PASAK BUMI ROOT AND PROPOLIS EXTRACTS ON PARASITEMIA LEVELS IN MICE INFECTED WITH PLASMODIUM BERGHEI - HASANAH, NUR; ASTUTY, HENDRI (International Journal of Applied Pharmaceutics, 2019)
Objective: Malaria infection remains a global concern due to increasing resistance to artemisinin-based combination therapy. This study examined the antimalarial effects of propolis extract alone and in combination with pasak bumi root extract. Methods: In the study, 30 mice were divided into six groups including two control groups, two groups of mice treated with propolis alone at concentrations of 90 and 180 mg/kg body weight (BW), and two combination groups of mice treated with 90 or 180 mg/kg BW propolis in combination with 60 or 75 mg/kg BW pasak bumi, respectively. Plasmodium berghei 2% was injected into each mouse, and blood smears were prepared after 8 days to assess parasitemia. Results: The results revealed no significant difference in parasitemia levels between the positive control and the two combination groups (p=0.136 and 0.289, respectively). However, superior growth inhibition (GI) results were observed in the combination groups (97.97% and 97.83%, respectively) than in the propolis monotherapy groups, whereas better outcomes were observed in the positive control group (98.63% GI) than in the propolis monotherapy groups (23.88% and 51.66%, respectively). Conclusion: These results illustrate that combination therapy is superior to propolis monotherapy in inhibiting parasitemia.